2008
DOI: 10.1177/1069072707313198
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Perceived Teacher Support and Its Influence on Adolescent Career Development

Abstract: This article examines available measures of perceived teacher support and presents findings from two studies exploring the psychometric properties of the Teacher Support Scale (TSS). In Study 1, an exploratory factor analysis suggested a hierarchical structure with four first-order factors (Invested, Positive Regard, Expectations, and Accessible subscales) loading onto a single, higher order factor, excellent reliability, and concurrent validity. Perceived teacher support was significantly correlated with care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
130
2
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(153 citation statements)
references
References 54 publications
8
130
2
13
Order By: Relevance
“…For example, adolescents who perceived their teachers to be supportive, had more confidence in their career decision-making ability (Metheny, McWhirter, & O'Neil, 2008). A lack of perceived support from either teachers or parents, on the other hand, resulted in adolescents feeling uncertainty about their careers (Constantine, Wallace, & Kindaichi, 2005;Metheny, McWhirter, & O'Neil, 2008).…”
Section: Sources Of Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, adolescents who perceived their teachers to be supportive, had more confidence in their career decision-making ability (Metheny, McWhirter, & O'Neil, 2008). A lack of perceived support from either teachers or parents, on the other hand, resulted in adolescents feeling uncertainty about their careers (Constantine, Wallace, & Kindaichi, 2005;Metheny, McWhirter, & O'Neil, 2008).…”
Section: Sources Of Supportmentioning
confidence: 99%
“…For example, adolescents who perceived their teachers to be supportive, had more confidence in their career decision-making ability (Metheny, McWhirter, & O'Neil, 2008). A lack of perceived support from either teachers or parents, on the other hand, resulted in adolescents feeling uncertainty about their careers (Constantine, Wallace, & Kindaichi, 2005;Metheny, McWhirter, & O'Neil, 2008). Family and monetary support predicted happiness in a sample of married adults (North, Holahan, Moos, & Cronkite, 2008), while Lett and colleagues (2005) examined functional support in a group of patients with heart disease and found that low levels of support resulted in a 1.5 to 2.0 fold increased risk for mortality and morbidity.…”
Section: Sources Of Supportmentioning
confidence: 99%
“…96 in a sample with high school sophomores and Ludwig and Warren (2009) found .96 in a study with high school students. In addition, Metheny et al (2008) found Cronbach's alpha for investment (r =.92), positive regard (r =.89), expectations (r =88), and accessible (r =.85).…”
Section: Measurement Of Constructsmentioning
confidence: 97%
“…96 using a revised 25-item measure in a study with high school students. In addition, Metheny et al (2008) conducted internal consistency analyses on a 21-item measure and found internal consistency reliability coefficients using Cronbach's alpha for the following subscales: investment (α=.92), positive regard (α=.89), expectations (α= .88), and accessible (α =.85) to be acceptable. In the current study, we used the 25-item TSSR which was revised by Ludwing and Warren (2009).…”
Section: Teacher Supportmentioning
confidence: 99%
See 1 more Smart Citation